The cost of abatement options to reduce carbon emissions from Australian international flights. Issue 3 (16th March 2018) - Yin, Kwong-sang; Ward, Adrian; Dargusch, Paul; Halog, Anthony
ABSTRACT: In 2012, a total of 13.1 million tonnes of carbon dioxide were emitted by 14 airlines while transporting 72 per cent of international passengers into and out of Australia in 2012. With passenger and cargo traffic growing at between five to six per cent annually from 2013 to 2033, acquiring more fuel efficient aircraft to both renew the existing fleet and to service growth has the greatest potential in reducing emissions over the next 20 years. Our analysis shows that implementing carbon dioxide emissions abatement options such as installing light weight seats, iPad electronic flight bags, winglets, washing aircraft engines and reducing the number of engines used during taxiing, all offer net financial savings when considered over 20 years. Acquiring new fuel efficient aircraft has the biggest impact on emissions reduction. Low interest loans and longer loan repayment periods may incentivise airlines to acquire more fuel efficient aircraft to service traffic growth but other complimentary incentives and penalties are required to influence airlines to replace their current fleet with more fuel efficient aircraft.